Sporotrichosis in a domestic Cat. Report of the first case in Ecuador - Zúñiga-Valencia, Mónica Salomé; Ordoñez, Andrés Renato; Cunha, Felipe Rosa; Guerrero-López, Ana Elizabeth (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
Sporotrichosis is a mycosis caused by pathogenic species of Sporothrix schenkii. Clinical manifestations in cats cause skin lesions such as nodules and ulcers. The objective of this work was to report a case of an entire male feline of approximately six years of age, which presented a 12 centimeters (cm) mass on the head, of solid consistency, wide base and highly vascularized. Complete blood test and test to rule out viral diseases was requested. The results were positive for Feline Viral Leukemia, in the blood count pancytopenia was observed with a hematocrit of 11 %. Fine needle aspiration cytology was performed, under the microscope it was possible to differentiate degenerated neutrophils and oval microorganisms with an unstained halo and a basophilic center. With the result, a sample of the tissue was taken and sent for mycological culture in Sabouraud agar and this revealed blackish-brown colonies. There was a favorable response to treatment with itraconazole and baths with Chlorhexidine plus Miconazole shampoo. After 90 days (d), an average scar of 1 cm was observed and when performing a cytology, no content or cellularity was observed with the stain. Treatment was suspended at 90 d. This is the first documented report of sporotrichosis in a feline in Ecuador